RAGAM BAHASA PRANCIS DALAM MAJALAH DIGITAL BUMBU - Qulby, Anisa Mutiara; Laksman-Huntley, Myrna (Universitas Hasanuddin, 2024)
French has several types of language varieties known as Registres de langue, including soutenu, courant, and familier. These varieties are used depending on the context of communication, the interlocutor, and the communication situation. This qualitative research aims to identify the types of language varieties used in Bumbu digital magazine. T Courant variety dominates the articles in the first three editions of the magazine. In this way, the target audience becomes wider because anyone will easily understand the contents of Bumbu magazine articles. Misunderstandings that may arise can be avoided. These findings support the view that language use in a news context can reflect the subjectivity of journalists (Bentounsi, 2021). The increase in the number of sentences and types of sentences in the three articles shows an increase in the ability to compose articles in French as well as adaptation and development in presenting information.